Clinical significance and related factors of rectal hyposensitivity in patients with functional defecation disorder - Jiang, Ya; Wang, Yan; Wang, Meifeng; Lin, Lin; Tang, Yurong (Frontiers in Medicine, 2023)
Background Rectal hyposensitivity (RH) is not uncommon in patients with functional defecation disorder (FDD). FDD patients with RH are usually unsatisfied with their treatment. Aims The aim of this study was to find the significance of RH in patients with FDD and the related factors of RH. Methods Patients with FDD first completed clinical questionnaires regarding constipation symptoms, mental state, and quality of life. Then anorectal physiologic tests (anorectal manometry and balloon expulsion test) were performed. Rectal sensory testing (assessing rectal response to balloon distension using anorectal manometry) was applied to obtain three sensory thresholds. Patients were separated into three groups (non-RH, borderline RH, and RH) based on the London Classification. The associations between RH and clinical symptoms, mental state, quality of life, and rectal/anal motility were investigated. Results Of 331 included patients with FDD, 87 patients (26.3%) had at least one abnormally elevated rectal sensory threshold and 50 patients (15.1%) were diagnosed with RH. Patients with RH were older and mostly men. Defecation symptoms were more severe (p = 0.013), and hard stool (p < 0.001) and manual maneuver (p = 0.003) were more frequently seen in the RH group. No difference in rectal/anal pressure was found among the three groups. Elevated defecatory desire volume (DDV) existed in all patients with RH. With the number of elevated sensory thresholds increasing, defecation symptoms got more severe (r = 0.35, p = 0.001). Gender (male) (6.78 [3.07–15.00], p < 0.001) and hard stool (5.92 [2.28–15.33], p < 0.001) were main related factors of RH. Conclusion Rectal hyposensitivity plays an important role in the occurrence of FDD and is associated with defecation symptom severity. Older male FDD patients with hard stool are prone to suffer from RH and need more care.